1990
DOI: 10.1016/0014-5793(90)80876-k
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X‐ray crystallographic study of interleukin‐8

Abstract: Interleukin-8 (neutrophil-activating factor; NAP-i) has been crystallized by the vapour diffusion technique to give single crystals suitable for threedimensional structural study at a resolution higher than 2.4 A. The crystals belong to the space group P3,21 or P3=21 and have unit cell dimensions a=b=40.9A,c=90.3A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Identical crystals have also been grown using chemically synthesized protein. Recently, workers at Sandoz Pharmaceutical have reported that crystals apparently identical to the ones described here could be grown from polyethylene glycol at pH 6.5 (20). The crystals contain a monomer in the asymmetric unit.…”
Section: Methodssupporting
confidence: 67%
“…Identical crystals have also been grown using chemically synthesized protein. Recently, workers at Sandoz Pharmaceutical have reported that crystals apparently identical to the ones described here could be grown from polyethylene glycol at pH 6.5 (20). The crystals contain a monomer in the asymmetric unit.…”
Section: Methodssupporting
confidence: 67%
“…This cytokine was termed interleukin-8 (IL-8) [29]. Subsequently, it has been shown that many cell types other than monocytes, including blood monocytes, alveolar macrophages, fibroblasts, endothelial cells, and epithelial cells, can produce large quantities of IL-8 or IL-8 mRNA, in response to stimulation with endotoxin, IL-l, or tumor necrosis factor [8,30]. The functional study revealed that IL-8 overexpressed on some tumor cells, and that tumor-derived IL-8 through autocrine and paracrine could alter the composition of immune infiltrates in the tumor microenvironment and induce angiogenesis and growth of the cancer cells [31], which even involved in EMT and CSC-like change.…”
Section: Discussionmentioning
confidence: 99%